(untitled) - Odian, George (New York, 1994)
The book covers course fundamentals and supplements any class text; teaches effective problem-solving techniques. It includes 1.442 solved problems with complete solutions, also includes 544 supplementary problems answers.
Keywords: Chemistry,Chemistry, organic